Evidence of the neuroprotective potential of NeuroEPO in preclinical studies and clinical trials; A systematic review - Gisselle Fernández Peña; Carlos Luis Pérez Hernández; Olivia Ileana Román Guerra; Tammy Fernández Romero (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: Neuroprotection is an essential purpose in the treatment of neurological disorders and several investigations have evaluated the usefulness of NeuroEPO in preclinical studies and clinical trials. Objective: To evaluate the neuroprotective potential of NeuroEPO in neurological disorders. Material and Methods: A systematic review of original articles in Spanish and English was conducted using PRISMA methodology, guided by the question: Is NeuroEPO a safe and effective therapeutic candidate for neuroprotection in neurological disorders? LILACS and PubMed databases, and Google Scholar search engine were used. Results: With the strategy followed, a total of 20 articles were included for synthesis and review. Preclinical studies were conducted in biomodels of cerebral ischemia and Alzheimer's disease, while clinical trials were conducted in patients with neurodegenerative diseases. Safety, tolerability, and efficacy of NeuroEPO were found when administered intranasally with varying doses, frequency of administration, and duration of intervention. Neuroprotective effects were observed in all studies, and some molecular mechanisms mediating these effects were evidenced. Conclusions: NeuroEPO has been reported to be a safe product, without hematopoietic effects, and well tolerated intranasally, which provides benefits in conditions of ischemic or degenerative brain damage by stimulating endogenous neuroprotection mechanisms with antioxidant, anti-inflammatory, and antiapoptotic action. The results support the continuity of studies aimed at enriching the scientific evidence of the potential of NeuroEPO for the treatment of neurological disorders